x nhân 1/2 = 3 +4/9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{1}{9}.3^4.3^x=3^7\)
\(\Leftrightarrow3^x=3^7:\frac{1}{9}:3^4=243\)
\(\Leftrightarrow3^x=3^5\)
\(\Leftrightarrow x=5\)
x * 4/3 - x *1/3 = 2/9
x * (4/3-1/3) = 2/9
x * 1 = 2/9
x = 2/9
\(x\cdot\frac{4}{3}-x\cdot\frac{1}{3}=\frac{2}{9}\)
\(x\cdot\frac{4-1}{3}=\frac{2}{9}\)
\(x\cdot1=\frac{2}{9}\)
\(x=\frac{2}{9}:1\)
\(x=\frac{2}{9}\)
Ta có : \(\left[x\cdot\frac{1}{2}+2\right]:\frac{3}{5}+4=9.\)
=> \(\left[x\cdot\frac{1}{2}+2\right]:\frac{3}{5}=9-4.\)
=> \(\left[x\cdot\frac{1}{2}+2\right]:\frac{3}{5}=5.\)
=> \(x\cdot\frac{1}{2}+2=5\cdot\frac{3}{5}.\)
=> \(x\cdot\frac{1}{2}+2=3.\)
=> \(x\cdot\frac{1}{2}=3+2.\)
=> \(x\cdot\frac{1}{2}=5.\)
=> \(x=5:\frac{1}{2}.\)
=> \(x=5\cdot2.\)
=> \(x=10.\)
Vậy x = 10 .
a)\(\left[x\times\frac{1}{2}+2\right]:\frac{3}{5}+4=9\) b)\(x\times\frac{2}{3}-\frac{1}{5}=\frac{2}{5}+1\)
\(\left[x\times\frac{1}{2}+2\right]:\frac{3}{5}=9-4\) \(x\times\frac{2}{3}-\frac{1}{5}=\frac{7}{5}\)
\(\left[x\times\frac{1}{2}+2\right]:\frac{3}{5}=5\) \(x\times\frac{2}{3}=\frac{7}{5}+\frac{1}{5}\)
\(x\times\frac{1}{2}+2=5\times\frac{3}{5}\) \(x\times\frac{2}{3}=\frac{8}{5}\)
\(x\times\frac{1}{2}+2=3\) \(x=\frac{8}{5}:\frac{2}{3}\)
\(x\times\frac{1}{2}=3-2\) \(x=\frac{8}{5}\times\frac{3}{2}\)
\(x\times\frac{1}{2}=1\) \(x=\frac{12}{5}\)
\(x=1:\frac{1}{2}\)
\(x=2\)
\(A=\frac{1}{2}+\frac{1}{6}+\frac{1}{12}+\frac{1}{20}+\frac{1}{30}+\frac{1}{42}\)
= \(\frac{1}{1.2}+\frac{1}{2.3}+\frac{1}{3.4}+\frac{1}{4.5}+\frac{1}{5.6}+\frac{1}{6.7}\)
= \(1-\frac{1}{2}+\frac{1}{2}-\frac{1}{3}+\frac{1}{3}-\frac{1}{4}+\frac{1}{4}-\frac{1}{5}+\frac{1}{5}-\frac{1}{6}+\frac{1}{6}-\frac{1}{7}\)
= \(1-\frac{1}{7}\)
= \(\frac{7}{7}-\frac{1}{7}\)
= \(\frac{6}{7}\)
2) \(\frac{7}{4}-x.\frac{4}{3}=\frac{5}{19}\)
\(x.\frac{4}{3}=\frac{7}{4}-\frac{5}{19}\)
\(x.\frac{4}{3}=\frac{133}{76}-\frac{20}{76}\)
\(x.\frac{4}{3}=\frac{113}{76}\)
\(x=\frac{113}{76}:\frac{4}{3}\)
\(x=\frac{399}{304}\)
VẬY \(x=\frac{399}{304}\)
b) \(\left(x+\frac{3}{4}\right).\frac{5}{7}=\frac{10}{9}\)
\(\left(x+\frac{3}{4}\right)=\frac{10}{9}:\frac{5}{7}\)
\(x+\frac{3}{4}=\frac{14}{9}\)
\(x=\frac{14}{9}-\frac{3}{4}\)
\(x=\frac{29}{36}\)
Vậy \(x=\frac{29}{36}\)
c) \(x.\frac{1}{2}+\frac{3}{2}.x=\frac{4}{5}\)
\(x.\left(\frac{1}{2}+\frac{3}{2}\right)=\frac{4}{5}\)
\(x.2=\frac{4}{5}\)
\(x=\frac{4}{5}:2\)
\(x=\frac{2}{5}\)
Vậy \(x=\frac{2}{5}\)
Chúc bạn học tốt !!!
6 2/7 + 7 3/5 + 8 6/9 + 9 1/4 + 2/5 + 5/7 + 1/3 x 3/4 + 1967
= 44/7 + 38/5 + 78/9 + 37/4 + 2/5 + 5/7 + 1/3 + 1967
= ( 44/7 + 5/7 ) + ( 38/5 + 2/5 ) + ( 26/3 + 1/3 ) + ( 37/4 + 3/4 ) +1967
= 7 + 8 + 9 + 10 + 1967
= 15 + 9 + 10 + 1967
= 24 + 10 + 1967
= 34 + 1967
= 2001
a,
x+x×14÷27+x÷29=255�+�×14÷27+�÷29=255
⇒x+x×14×72+x×92=255⇒�+�×14×72+�×92=255
⇒x+x×78+x×92=255⇒�+�×78+�×92=255
⇒x.(1+78+92)=255⇒�.(1+78+92)=255
⇒x⋅518=255⇒�⋅518=255
⇒x=255÷518⇒�=255÷518
⇒x=255×851⇒�=255×851
⇒x=40⇒�=40
Vậy x = 40
\(\sqrt{9.\left(x-1\right)^2}-12=0\)
=> 3.(x - 1) - 12 = 0
=> 3x - 15 = 0
=> 3x = 15
=> x = 5
b) \(\sqrt{4.\left(3-x\right)}=16\) (ĐKXĐ: x ≤ 3)
\(\Rightarrow\sqrt{3-x}=8\)
=> 3 - x = 64
=> x = -61
\(\left(\frac{1}{1.2.3}+\frac{1}{2.3.4}+...+\frac{1}{8.9.10}\right).x=\frac{23}{45}\)
\(\left(\frac{1}{1.2}-\frac{1}{2.3}+\frac{1}{2.3}-\frac{1}{3.4}+...+\frac{1}{8.9}-\frac{1}{9.10}\right).x=\frac{23}{45}\)
\(\left(\frac{1}{1.2}-\frac{1}{9.10}\right).x=\frac{23}{45}\)
\(\frac{22}{45}.x=\frac{23}{45}\)
\(x=\frac{23}{45}:\frac{22}{45}\)
\(x=\frac{23}{22}\)
\(\left(\frac{1}{1.2.3}+\frac{1}{2.3.4}+...+\frac{1}{8.9.10}\right)x=\frac{23}{45}\)
\(\Rightarrow\left(\frac{2}{1.2.3}+\frac{2}{2.3.4}+...+\frac{2}{8.9.10}\right).\frac{x}{2}=\frac{23}{45}\)
\(\Rightarrow\left(\frac{1}{1.2}-\frac{1}{2.3}+\frac{1}{2.3}-\frac{1}{3.4}+...+\frac{1}{8.9}-\frac{1}{9.10}\right)x=\frac{46}{45}\)
\(\Rightarrow\left(\frac{1}{1.2}-\frac{1}{9.10}\right)x=\frac{46}{45}\)
\(\Rightarrow\frac{22}{45}.x=\frac{46}{45}\Rightarrow x=\frac{46}{22}=\frac{23}{11}\)
`x xx 1 / 2 = 3 + 4 / 9`
`x xx 1 / 2 = 27 / 9 + 4 / 9`
`x xx 1 / 2 = 31 / 9`
`x = 31 / 9 : 1 / 2`
`x = 31 / 9 xx 2`
`x = 62 / 9`
x nhân 1/2 = 3/1 + 4/9
x nhân 1/2 = 27/9 + 4/9
x nhân 1/2 = 31/9
x = 31/9 : 1/2
x = 31/9 nhân 2/1
x = 62/9
chúc bạn học tốt !